Post COVID-19 world : will it reshape global leadership? - Ho, Benjamin Tze Ern (2020)
The COVID-19 pandemic has accentuated political fissures within the international community, worsening the ongoing US-China competition. While the post COVID-19 world remains unclear, the contest for international leadership will go on.